American Catholic Attitudes toward Jews, Judaism, and the Israeli-Palestinian Conflict - Bumin, Kirill; Cunningham, Philip A.; Gregerman, Adam; Inbari, Motti (Studies in Christian-Jewish Relations, 2023)
This unprecedented survey of a representative sample of American Catholics assesses their opinions about their Jewish neighbors, Judaism, Israel and Palestine, and Catholic Church teaching on these subjects. After comparing the survey's results with similar research on the views of evangelical Christians, the article focuses on implications for Catholic religious education, including the respondents' familiarity with relevant post-Nostra Aetate theological developments in papal and Vatican documents.